Cover Image. Issue 7 (29th July 2021) - Hamana, Tomoyo; Yamamoto, Hiroyuki; Sawada, Takahiro; Kawai, Hiroya; Takaya, Tomofumi
Abstract : The cover image is based on the Case Report Additional ablation effect of low‐speed rotational atherectomy following high‐speed rotational atherectomy on early calcifi ed in‐stent restenosis: a case report by Hiroyuki Yamamoto et al., https://doi.org/10.1002/ccr3.4550 .